Active site loop conformation regulates promiscuous activity in a lactonase from Geobacillus kaustophilus HTA426. - Yu Zhang; Jiao An; Guang-Yu Yang; Aixi Bai; Baisong Zheng; Zhiyong Lou; Geng Wu; Wei Ye; Hai-Feng Chen; Yan Feng; Giuseppe Manco (PLoS ONE)
Enzyme promiscuity is a prerequisite for fast divergent evolution of biocatalysts. A phosphotriesterase-like lactonase (PLL) from Geobacillus kaustophilus HTA426 (GkaP) exhibits main lactonase and promiscuous phosphotriesterase activities. To understand its catalytic and evolutionary mechanisms, we investigated a "hot spot" in the active site by saturation mutagenesis as well as X-ray crystallographic analyses. We found that position 99 in the active site was involved in substrate discrimination. One mutant, Y99L, exhibited 11-fold improvement over wild-type in reactivity (kcat/Km) toward the phosphotriesterase substrate ethyl-paraoxon, but showed 15-fold decrease toward the lactonase substrate δ-decanolactone, resulting in a 157-fold inversion of the substrate specificity. Structural analysis of Y99L revealed that the mutation causes a ∼6.6 Å outward shift of adjacent loop 7, which may cause increased flexibility of the active site and facilitate accommodation and/or catalysis of organophosphate substrate. This study provides for the PLL family an example of how the evolutionary route from promiscuity to specificity can derive from very few mutations, which promotes alteration in the conformational adjustment of the active site loops, in turn draws the capacity of substrate binding and activity.